2015
DOI: 10.1038/srep09175
|View full text |Cite
|
Sign up to set email alerts
|

Non-local classical optical correlation and implementing analogy of quantum teleportation

Abstract: This study reports an experimental realization of non-local classical optical correlation from the Bell's measurement used in tests of quantum non-locality. Based on such a classical Einstein–Podolsky–Rosen optical correlation, a classical analogy has been implemented to the true meaning of quantum teleportation. In the experimental teleportation protocol, the initial teleported information can be unknown to anyone and the information transfer can happen over arbitrary distances. The obtained results give nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…As a consequence of the mathematical similarity between the Hilbert spaces of multi-partite quantum states and multi-DoF classical optical fields, a corresponding concept of classical entanglement indicates the non-separability of the beam into uncoupled DoFs. After the initial suggestion by Spreeuw 19 , a substantial body of work has accumulated in the past five years in which classical entanglement is exploited in solving long-standing problems in polarization optics 27 28 29 , delineating the contributions of non-separability and intrinsic randomness to the coherence of an optical beam 10 30 , introducing new metrology schemes 31 , and implementing classical analogs of quantum information processing protocols, such as teleportation 32 33 , and super-dense coding, etc.…”
mentioning
confidence: 99%
“…As a consequence of the mathematical similarity between the Hilbert spaces of multi-partite quantum states and multi-DoF classical optical fields, a corresponding concept of classical entanglement indicates the non-separability of the beam into uncoupled DoFs. After the initial suggestion by Spreeuw 19 , a substantial body of work has accumulated in the past five years in which classical entanglement is exploited in solving long-standing problems in polarization optics 27 28 29 , delineating the contributions of non-separability and intrinsic randomness to the coherence of an optical beam 10 30 , introducing new metrology schemes 31 , and implementing classical analogs of quantum information processing protocols, such as teleportation 32 33 , and super-dense coding, etc.…”
mentioning
confidence: 99%
“…It has been shown recently that the classical electrodynamics contains a Hilbert space structure which makes it similar to quantum mechanics in certain aspects [33]. In addition to that, in recent experiments, researchers have explored the non-quantum entanglement (classical entanglement) in the classical optical field [34,35]. It is well known that the Maxwell's equations of the transverse modes of the electric field in an optical fiber can be transformed into an Optical-Schrödinger equation, where the z-axis of the optical fiber is analogous to time [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the quantum bound exists similarly in classical microwaves. The local and nonlocal correlations in the classical optical beams, which violate the Bell inequality, have been demonstrated in a series of works3435363738394041. However, the KCBS contextuality has not been studied in classical wave systems so far.…”
mentioning
confidence: 99%